(x^2-4x)(x^2-4x-1)-20
JinKazama1:
What is asked?
Answers
Answered by
6
Final Answer :
![{(x - 2)}^{2} (x - 5)(x + 1) {(x - 2)}^{2} (x - 5)(x + 1)](https://tex.z-dn.net/?f=+%7B%28x+-+2%29%7D%5E%7B2%7D+%28x+-+5%29%28x+%2B+1%29)
Steps:
1)
![( {x }^{2} - 4x)( {x }^{2} - 4x - 1) - 20 \\ = > {( {x}^{2} - 4x)}^{2} - ( {x }^{2} - 4x) - 20 ( {x }^{2} - 4x)( {x }^{2} - 4x - 1) - 20 \\ = > {( {x}^{2} - 4x)}^{2} - ( {x }^{2} - 4x) - 20](https://tex.z-dn.net/?f=%28+%7Bx+%7D%5E%7B2%7D++-+4x%29%28+%7Bx+%7D%5E%7B2%7D++-+4x+-+1%29+-+20+%5C%5C+%3D++%26gt%3B++%7B%28+%7Bx%7D%5E%7B2%7D++-+4x%29%7D%5E%7B2%7D++-+%28+%7Bx+%7D%5E%7B2%7D++-+4x%29+-+20+)
Let
![t = {(x}^{2} - 4x) t = {(x}^{2} - 4x)](https://tex.z-dn.net/?f=t+%3D++%7B%28x%7D%5E%7B2%7D++-+4x%29)
2)
![{t}^{2} - t - 20 \\ (t - 5)(t + 4) \\ = > ( {x}^{2} - 4x - 5)( {x}^{2} - 4x + 4) \\ = > (x - 5)(x + 1) {(x - 2)}^{2} {t}^{2} - t - 20 \\ (t - 5)(t + 4) \\ = > ( {x}^{2} - 4x - 5)( {x}^{2} - 4x + 4) \\ = > (x - 5)(x + 1) {(x - 2)}^{2}](https://tex.z-dn.net/?f=+%7Bt%7D%5E%7B2%7D++-+t+-+20+%5C%5C+%28t+-+5%29%28t+%2B+4%29+%5C%5C++%3D++%26gt%3B+%28+%7Bx%7D%5E%7B2%7D++-+4x+-+5%29%28+%7Bx%7D%5E%7B2%7D++-+4x+%2B+4%29+%5C%5C++%3D++%26gt%3B+%28x+-+5%29%28x+%2B+1%29+%7B%28x+-+2%29%7D%5E%7B2%7D+)
Steps:
1)
Let
2)
Answered by
4
Answer:
Step-by-step explanation:
(x²-4x)(x²-4x-1)-20
=x⁴-4x³-x²-4x³+16x²+4x-20
=x⁴-8x³+15x²+4x-20
Similar questions